Effect of Small Organic Acid Anions on the Adsorption of Phosphate Anions onto Synthetic Goethite from Aqueous Solution - Zhongliang Shi; Fang Li; Shuhua Yao (Adsorption Science & Technology)
Batch experiments were conducted to study the effect of small organic acids (citric, oxalic and acetic) on the removal of phosphate anions from aqueous systems using synthesized goethite as the adsorbent. The results showed that phosphate anion adsorption was most significantly inhibited by citric among the three organic acids studied. Phosphate anion adsorption was affected at pH values below 6.5. The relationship between citrate anionpromoted goethite dissolution and citrate anion-suppressed phosphate anion adsorption in equilibrated goethite–phosphate anion–citric acid systems with different contact orders was studied. The results indicated that there is an obvious correlation between the suppression of phosphate anion adsorption and the dissolution of goethite. It is proposed that competition for binding sites play a key role in the reduction of phosphate anion adsorption by citric acid.